The Security aspects in the Arctic: the potential Role of NATO - Irina Zhilina (Nordicum-Mediterraneum, 2013)
This paper addresses military security issues in the Arctic region and assesses in particular NATO’s Arctic agenda by giving a historical retrospective on the militarization of the High North. Also, it provides a theoretical background to understand the contemporary strategic situation and analyze how the enduring nuclear-weapon-based security strategies can influence the future international relations in the Arctic.